The Access to Antenatal and Postpartum Care Services of Migrant Workers in the Greater Mekong Subregion: The Role of Acculturative Stress and Social Support - Charamporn Holumyong; Kathleen Ford; Siriporn Sajjanand; Aphichat Chamratrithirong (Journal of Pregnancy)
The objective of this paper is to determine whether social support and acculturative stress were related to obtaining antenatal and postpartum care for pregnant female migrants, as well as access to health care for migrant children. The study utilized data of 987 migrant workers in Thailand who originated from hill tribes and mountain communities in Myanmar and Cambodia. Regression analysis showed that the language barrier, a crucial factor behind acculturative stress, adversely influenced access to maternal care. Social support reduced the impact of acculturative stress. Migrants with support are more likely to access health care. Based on the Multidimensional Scale of Perceived Social Support, more sources of support either from friends, family members, or other supporters who are significant could increase health care access. Besides friends and family, the support from the Migrant Health Worker Program and Migrant Health Volunteer Program allowed the formal health sector to utilize the informal social networks to improve care for migrants.